Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Matematika di SMKN 1 Praya Tengah - Mahdi Putra Jaya (Jurnal Paedagogy, 2022)
This study aims to increase students' motivation to learn mathematics on the subject of circles through the application of a team games tournament (TGT) type of cooperative learning model. This research is a classroom action research which consists of two cycles and each of them consists of four main activities, namely planning, action, observation, and reflection in an interrelated spiral. The subjects of this study were students of class X Accounting at SMKN 1 Praya Tengah, totaling 32 people. Data collection instruments in the form of questionnaires and observations as well. While the data analysis technique used descriptive analysis. The results of this study indicate that students' learning motivation on the subject of the circle has increased from cycle I to cycle II. The attention aspect of the first cycle at the first meeting was 18.75%, the second meeting was 56.25%, in the second cycle 81.25%. The tenacity aspect of the first cycle of the first meeting was 12.50%, the second meeting was 50%, the second cycle was 75%. Aspects of perseverance in the first cycle of the first meeting 25%, at the second meeting 56.25%, the second cycle 87.5%. The interest aspect of the first cycle of the first meeting is 6.25%, the second meeting is 43.75%, the second cycle is 75%. The courage aspect of the first cycle of the first meeting was 18.75%, and the first cycle of the second meeting was 56.25%, the second cycle was 81.25%. The results of the motivation questionnaire in the first cycle of the first meeting were 50.42%, in the first cycle the second meeting was 80.42% and increased in the second cycle to 92.92%. So it can be concluded that cooperative learning of the type of teams games tournament (TGT) can increase students' learning motivation on the subject of circles in class X Accounting at SMKN 1 Praya Tengah.